On some characteristics of the claim surplus process - Gusak, D. (Інститут математики НАН України, 2008)
The distribution of characteristics, which describes the behaviour of the claim surplus process after the ruin, is investigated and compared with some previous results on distributions of risk functionals. Main attention is given to total durations of a sojourn time for risk processes in a risk (red) zone and in a survival (green) zone.